Implementasi Wanita Agen Pancasila: Pemberdayaan Ibu-Ibu PKK Melalui Pelatihan Pembuatan Selai Kopi dan Body Scrub Sebagai Upaya Peningkatan UMKM di Desa Jurangmangu Kecamatan Pulosari Kabupaten Pemalang - Kirana May Muna, Kirana; Rizkha Fatmawati; Eka Titi Andaryani (Jurnal Bina Desa, 2025)
Jurangmangu Village is the smallest village in Pulosari District, Pemalang Regency, Central Java, Indonesia. Jurangmangu Village consists of 2 hamlets, namely Cikunang Hamlet and Krajan Hamlet, which are divided into 7 RTs and 2 RWs. The topographic condition of Jurangmangu Village consists of a plateau which has a height of 1200 meters above sea level and is close to Mount Slamet. The population in Jurangmangu Village at the end of 2022 was 1,344 people, consisting of 672 men and 672 women. Commodities that still exist today in Jurangmangu Village are coffee and tobacco plants. This tobacco plant is sold in various areas such as Parakan, Wonosobo, Temanggung and Magelang. Meanwhile, the coffee is processed by yourself and sold by word of mouth which is spread from cafe to cafe. Jurangmangu Coffee is managed by the Tunas Cikunang Group under the name D'Jav Coffe which was founded in 2018. Jurangmangu Village still has minimal use of the internet, during the 5 years it has been established the farmer group has experienced difficulties in promoting and marketing D'Jav Coffe products, especially via the internet. This causes the general public to be less familiar with D'Jav Coffee coffee products and unable to compete with other coffee products. Conditions like this will reduce selling power and will not be able to meet the targets expected by the Tunas Cikunang Farmers Group. The type of research used in this service research is qualitative research. The results of this research are to produce products with the aim of improving MSMEs in Jurangmangu Village. This service activity is used to implement the Women Agents of Pancasila. Jurangmangu Village was chosen as a Pancasila Activator Village which has indicators of success in producing products or services from training or mentoring activities for women's community groups targeting PKK women in Jurangmangu Village. The Jurangmangu Village Group held training on making coffee jam and body scrub which aims to improve MSMEs, improve the economy and open up job opportunities in Jurangmangu Village. With this training, PKK women will practice directly making coffee jam and body scrub using Jurangmangu Coffee as the main ingredient.